Evaluation of CSF pyrosequencing to diagnose tuberculous meningitis: A retrospective diagnostic accuracy study. (January 2021) - Ajbani, Kanchan; Kazi, Mubin; Agrawal, Umang; Jatale, Raj; Soman, Rajeev; Sunavala, Ayesha; Shetty, Anjali; Rodrigues, Camilla
Abstract: Background: We evaluated the performance of pyrosequencing, a genotypic test which detects TB and XDR-defining mutations within 6 h, directly on CSF samples for diagnosing TB meningitis(TBM). Methods: This retrospective, diagnostic accuracy study was conducted in Hinduja hospital, Mumbai from May-2017 to May-2019. 107 consecutive patients with physician-suspected TBM for whom CSF pyrosequencing was requested were screened. Seven patients with incomplete data were excluded. Diagnostic accuracy of pyrosequencing was compared with Xpert MTB/Rif and TBMGIT (TB Mycobacterial Growth Indicator Tube) culture against the uniform case definition of definite or probable TBM. Susceptibility concordance rate of pyrosequencing with TBMGIT culture and Xpert MTB/Rif was determined. Results: The study cohort comprised of 100 patients[Definite(n = 33), Probable(n = 20), Possible(n = 30), Alternative(n = 17)] with 50% males[median age(years):38(Range:2–87)]. Against the uniform case definition, pyrosequencing had 98·11%(95%CI 89·93–99·95; n = 52/53) sensitivity and 97·79%(86·31–99·67; n = 44/45) negative predictive value(NPV) compared with 43.39%(29·83–57·72; n = 23/53, p < 0.0001) sensitivity and 61.04%(55·31–66·48; n = 47/77) NPV for Xpert MTB/Rif and 45·28%(31·56–59·55; n = 24/53, p < 0.0001) sensitivity and 61·84%(55·92–67·43; n = 47/76) NPV for TBMGIT culture. Susceptibility concordance rate of pyrosequencing with phenotypic Drug Susceptibility Testing was 91.3%(n = 21/23) and with Xpert MTB/Rif was 95·45%(n = 21/22). Conclusion: CSF pyrosequencing is significantly more sensitive than Xpert MTB/Rif and TBMGIT culture for diagnosing TBM. Additionally, it facilitates early therapeutic decision-making by providing information on XDR-defining mutations. Highlights: The current gold standard diagnostics do not perform well in tuberculous meningitis. Pyrosequencing showed an excellent diagnostic performance in Tuberculous meningitis. Facilitates rapid diagnosis (within 6 h) when performed directly on CSF samples. Information provided about XDR-defining mutations optimises therapeutic management. Potentially life-saving implications in regions endemic for drug-resistant tuberculosis.